Make a better place for you and for me the effects of guilt frames on the intention to donate of middle-class university women ages 20-25 - Advincula, Via Alexandra Cadelina; San Pascual, Ma. Rosel; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2019)
Guilt frame is commonly used in charity appeals to gain support specifically in raising funds. Guilt frame is effective when individuals perceive that they have violated social norms to be altruistic. By appealing to their social responsibility and presenting a course of action, individuals are compelled to lessen or eliminate the feeling of guilt. Media studies have identified that various elements, such as actors, narrative, statistics, and exposure that can elicit guilt on a scale of low to high, can make them donate to the cause. This study uses the same guilt-inducing elements in an experiment that exposes middle-class university women to groups of either low level of guilt or high level of guilt. The findings of the study suggest that generally, women who are exposed to high level of guilt in charity appeals had significantly higher intention to donate compared with women exposed to low level of guilt. Furthermore, when these women have positive and high propensities to donate, it significantly increases their intention to donate. The study concludes that guilt frame is effective in increasing intention to donate when amplified with high level of perceived behavioral control and awareness of the advocacy.
Vita.
Thesis (A. B. Communication Research )--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Helping behavior -- Social aspects; Altruism -- Social aspects